STUDI POTENSI EKOWISATA DI DESA IKAN BANYAK KABUPATEN LIMAPULUH KOTA SUMATERA BARAT - Rahmat, Rahdian Adithia; Suryasih, Ida Ayu (JURNAL DESTINASI PARIWISATA; Vol 2 No 1 (2014): VOL 2, NO 1 (2014): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATA, 2014)
Abstract Ikan banyak is one of village. Ikan Banyak has ecotourism potentials which is consist of several various kind such us as physic and non physic. High potentials as mentioned above is not linier with citizen allife surround. Based on these background there might be research should be necessary to slove two kind of problems, they are describe what kind of ecotourism potentials belonging of Ikan Banyak and how to develop ecotourism potensials as tourism object. The result of this research states that Ikan Banyak  Village has physic sources such as : Sinamar River, Batu Balago Agriculture, Gosan, Sodah Cave, Batu Bulan Waterfall, andweather of Ikan Banyak. In other side Ikan Banyak has non physic potentials such as : Monyabik, Batagak Pangulu, Potang Balimau, and Mondua Basamo. Thus SWOT Analyzed produce strategy ecotourism development suc as SO,WO,ST,and WT strategy.
Keywords: Keyword : Ecotourism Potential, Developt Strategy, Development Step.